The "Enhancement" of Cultural Heritage by AMS Dating: Ethical Questions and Practical Proposals. Issue 2 (15th September 2016) - Huysecom, Eric; Hajdas, Irka; Renold, Marc-André; Synal, Hans-Arno; Mayor, Anne
Abstract: The looting of archaeological and ethnographic objects from emerging countries and areas of conflict has prospered due to the high prices that these objects can achieve on the art market. This commercial value now almost necessarily requires proof of authenticity by the object's age. To do so, absolute dating has been conducted since the end of the 1970s on terra cotta art objects using the thermoluminescence method, a practice that has since been condemned. It is only more recently, since the 2000s, that art dealers and collectors have begun to use the accelerator mass spectrometry (AMS) method to date different kinds of objects made of organic materials. Compared to conventional radiocarbon dating, the AMS technique requires only very small samples, thus depreciating neither the aesthetics nor commercial value of the object. As a result, the use of absolute dating has become widespread, accompanying the increase in looting of the cultural heritage of countries destabilized by political overthrows and armed conflicts, especially in the Near East and Africa. The present article condemns the practice of AMS dating of looted art objects and encourages the creation of a code of deontology for 14 C dating laboratories in order to enhance an ethical approach in this sensitive field facing the current challenges. RÉSUMÉ: Le pillage des biens archéologiques et ethnographiques au sein des pays émergents et des zones de conflits prospère du fait de la valeur importante que ces objets peuvent atteindre sur le marché de l'art. Cette valorisation commerciale se fait aujourd'hui quasi obligatoirement au moyen de la preuve de l'authenticité par l'ancienneté. Pour ce faire, des datations absolues ont été pratiquées depuis la fin des années 1970 sur des objets d'art en terre cuite à l'aide de tests de thermoluminescence, une pratique qui a été dénoncée depuis lors. Ce n'est que plus récemment, à partir des années 2000, que les marchands et collectionneurs ont commencé à avoir recours aux datations radiocarbones par la méthode "accelerator mass spectrometry" (AMS) pour dater divers types d'objets en matière organique. En comparaison des datations conventionnelles, cette technique ne nécessite en effet que des prélèvements de très petite taille, qui ne déprécient ni l'esthétique ni la valeur commerciale de l'objet. Depuis lors, on assiste à une généralis - ation de l'usage des datations absolues, qui accompagne l'accroissement du pillage du patrimoine culturel des pays déstabilisés par les renversements politiques et les conflits armés, tout particulièrement au Proche-Orient et en Afrique. Le présent article vise à dénoncer la pratique des datations AMS d'objets d'art de provenance illicite et à encourager la création d'un code de déontologie pour les laboratoires de datations radiocarbones, dans une perspective de respect de l'éthique dans ce domaine sensible et aux prises avec l'actualité.